Consumer perceptions of new wood-based products - Wallius, Venla (2019)
Combatting current, global environmental challenges such as climate change requires transition from fossil-based economy towards environmentally, economically and socially sustainable bioeconomy. Wood has proven to be a versatile and readily available material that is renewable and able to substitute for non-renewable, fossil-based, environmentally harmful materials. Wood has multiple traditional applications but it is also a potential material to many emerging products, such as textiles and chemicals.